HBR guide to crafting your purpose - Coleman, John, 1981- (Boston, Massachusetts : Harvard Business Review Press, 2022)
"Stop searching for purpose. Build it. We're living through a crisis of purpose. Surveys indicate that people feel less and less connected to the meaning of their work. Individuals everywhere are asking, "How can I find my purpose?" That's the wrong question. You don't find your purpose-you build it. The HBR Guide to Crafting Your Purpose debunks three misconceptions about purpose at work: that purpose is found, that you have only one, and that it remains the same over time. Packed with tips and advice for how you can cultivate more meaning in your life and at work, this book teaches you how to endow everything you do with purpose each day. You'll learn how to: find the reason behind your work, identify what makes you feel happy and engaged, use job crafting to transform your role, connect your work to service, build positive, fulfilling relationships, let go of past purposes-and take steps toward new ones, arm yourself with the advice you need to succeed on the job, with the most trusted brand in business. Packed with how-to essentials from leading experts, the HBR Guides provide smart answers to your most pressing work challenges"--
Section 1. Getting started with purpose: Purpose, and why it matters -- we're experiencing a crisis of meaning -- Identifying your starting point -- an exercise for focusing your efforts -- Section 2. Redefining how we think about purpose: Dispelling three common myths -- how do you find your purpose? You don't -- Mining your life for meaning -- where to look for what moves you -- The many sources of purpose in your life -- six spots purpose can live-at the same time -- Embracing shifts in purpose -- learn to let go -- Section 3. Building your purpose: Craft your work -- turn the job you have into the job you want -- Make work a craft -- aim for self-improvement and task mastery -- Connect your work to service -- at work, at home, and in your community -- Invest in positive relationships -- elevate connections with those in your network -- Section 4. Purpose in your organization: Creating a culture of purpose -- you don't have to be a top leader to have an impact -- Living into corporate purpose -- help colleagues understand and act on the mission -- Conclusion: A call to action.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 14, 2022).
WorldCat record variable field(s) change: 050
Keywords: Job enrichment; Quality of work life; Self-actualization (Psychology); Job enrichment; Quality of work life; Self-actualization (Psychology); elektronické knihy; electronic books